1992
DOI: 10.1128/jb.174.5.1568-1573.1992
|View full text |Cite
|
Sign up to set email alerts
|

arcD, the first gene of the arc operon for anaerobic arginine catabolism in Pseudomonas aeruginosa, encodes an arginine-ornithine exchanger

Abstract: In the absence of oxygen and nitrate, Pseudomonas aeruginosa metabolizes arginine via the arginine deiminase pathwayt, which allows slow growth on rich media. The conversion of arginine to ornithine, C02, and NH3 is coupled to the production of ATP from ADP. The enzymes of the arginine deiminase pathway are organized in the arcDABC operon. The arcD gene encodes a hydrophobic polytopic membrane protein.Translocation of arginine and ornithine in membrane vesicles derived from an Escherichia coli strain harboring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 35 publications
2
47
0
2
Order By: Relevance
“…The behavior of P. aeruginosa-and Climax Community-dominated samples matches much of what is recorded in the literature: that the organism grows anaerobically using denitrification in antibiotic-resistant biofilms (Worlitzsch et al, 2002;Palmer et al, 2005;Hogardt and Heesemann, 2010;Schobert and Jahn, 2010). The elevated pH in the media may be due to the production of ammonia from amino-acid breakdown, often observed with P. aeruginosa grown in a CF state (Verhoogt et al, 1992;Barth and Pitt, 1996;Thomas et al, 2000;Frimmersdorf et al, 2010), and previously demonstrated to accumulate in WinCF capillary tubes after the growth of CF microbes . Thus the P. aeruginosa WinCF responses may reflect the true physiology of this microbe and others like it in the CF lung and is in stark contrast to the physiology of the Attack Community during exacerbation events.…”
Section: Sources Of the Fermentative Responsesupporting
confidence: 59%
“…The behavior of P. aeruginosa-and Climax Community-dominated samples matches much of what is recorded in the literature: that the organism grows anaerobically using denitrification in antibiotic-resistant biofilms (Worlitzsch et al, 2002;Palmer et al, 2005;Hogardt and Heesemann, 2010;Schobert and Jahn, 2010). The elevated pH in the media may be due to the production of ammonia from amino-acid breakdown, often observed with P. aeruginosa grown in a CF state (Verhoogt et al, 1992;Barth and Pitt, 1996;Thomas et al, 2000;Frimmersdorf et al, 2010), and previously demonstrated to accumulate in WinCF capillary tubes after the growth of CF microbes . Thus the P. aeruginosa WinCF responses may reflect the true physiology of this microbe and others like it in the CF lung and is in stark contrast to the physiology of the Attack Community during exacerbation events.…”
Section: Sources Of the Fermentative Responsesupporting
confidence: 59%
“…The gene coding for lysine decarboxylase is located in an operon structure together with a gene which seems to code for a transport protein. On the basis of homology with the arginine/ornithine antiporter of P. aeruginosa (26), this transport protein was predicted to be a lysine/cadaverine antiporter.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the ArcD protein, which specifies an arginine/ornithine antiporter of Z? aeruginosa (Luthi et al, 1990;Verhoogt et al, 1992) and falls into the class of bacterial precursor/product antiporters discussed by Poolman (1990), is more divergent. The ArcD antiporter of P. aeruginosa is most similar to the two E. coli polyamine permeases, i.e., the putrescine/ornithine antiporter (PotE: Kashiwagi et al, 1991Kashiwagi et al, , 1992 and the putative cadaverine/lysine antiporter (CadB : Meng & Bennett, 1992;Watson et al, 1992) (24% identity; comparison scores of 23-33 standard deviations, see Table 1).…”
Section: Phylogenetic Relationships Among Members Ofthe Apc Familymentioning
confidence: 99%